IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DALAM MENANAMKAN KARAKATER POSITIF ANAK USIA DINI - Ndaru Putri Yudhiarti (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
Early childhood education is a fundamental phase in character formation, requiring a learning approach that can instill positive values from an early age. The Merdeka Curriculum introduces the Project for Strengthening Pancasila Student Profiles (P5) as one of the project-based learning strategies that emphasizes real, collaborative, and contextual experiences. This study aims to describe the implementation of P5 in instilling positive character in early childhood at TK Aisyiyah Banyubiru. The research employed a qualitative approach with a case study design. The research subjects consisted of teachers, students, and the school principal. Data were collected through observation, in-depth interviews, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that the implementation of P5 was carried out through various project activities such as planting, maintaining environmental cleanliness, participating in social sharing activities, and habituation of daily worship practices. These activities contributed to the development of positive character traits in children, including independence, responsibility, cooperation, discipline, environmental awareness, and religiosity. The implementation of P5 at TK Aisyiyah Banyubiru can serve as an effective strategy for instilling positive character in early childhood, in line with the objectives of the Merdeka Curriculum and the values of Islamic education.